2007
DOI: 10.1007/s11010-007-9427-4
|View full text |Cite
|
Sign up to set email alerts
|

The proximal GC-rich region of p16INK4a gene promoter plays a role in its transcriptional regulation

Abstract: p16(INK4a) plays a key role in control of cell cycle progression by negatively regulating the CDK4/6 activity. This study establishes that the p16(INK4a) minimal promoter region required for the transcription factor Sp1 function is mapped at 62 bp upstream of the translation initiation codon. This region is GC-rich and shown to interact specifically with Sp1. siRNA-induced Sp1 silencing resulted in the inhibition of the p16(INK4a) minimal promoter activity. Additionally, by using a promoter sequence-directed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Sp1 is a key regulator of p16 expression [188][189][190]. The proximal promoter of p16, a region essential for p16 expression, contains multiple Sp sites (Fig.…”
Section: P16mentioning
confidence: 99%
“…Sp1 is a key regulator of p16 expression [188][189][190]. The proximal promoter of p16, a region essential for p16 expression, contains multiple Sp sites (Fig.…”
Section: P16mentioning
confidence: 99%
“…Methylation of the promoter of the 5′-CpG island in the p16 gene is one of the most common mechanisms of p16 inactivation in PDAC, emphasizing the importance of an epigenetic mechanism in modulating tumor suppressor function in this disease[12]. The result of this silencing is an interference of binding of permissive transcription factors, such as SP1, and the recruitment of MBDs that can recruit other proteins like HDACs and lead to chromatin compaction [33](fig. 2).…”
Section: Dna-based Epigeneticsmentioning
confidence: 99%
“…Recently, it has been revealed that AT-rich consensus in the promoter region of the CpC2 and ERD1 genes may be critical for the responsiveness of the gene to dehydration or hormone ABA (Ditzer and Bartels, 2006;Tran et al, 2007). Wang et al (2007) have found that both the specific mutation of the proximal GC-rich (GC-box) region of p16 INK4a gene promoter and siRNA-induced transcription factor SP1 silencing resulted in the complete loss of its transcription regulation, indicating that GC-rich region of promoter is required for SP1 function, and plays a role in p16 INK4a gene transcription regulation. The studies by Fenoll et al (1990) showed that the upstream activating sequence (UAS) of the promoter from maize streak virus (MSV) contains a GC-rich element, which was responsible for the transcriptional activation and the binding of maize nuclear factors.…”
Section: Discussionmentioning
confidence: 99%